Effect of intra-articular injection of corticosteroid in the patients with osteoarthritis of the knee – A hospital-based cross-sectional study - Rajeev Reddy Kikkuri (Wolters Kluwer Medknow Publications, 2021)
Background: Osteoarthritis (OA) of the peripheral joints is frequently related with physical disability and decline in health-related quality of life, deciphering into a significant burden on people and humankind. Although IA corticosteroid injections are being in clinical use, their long-term effects on knee OA are least studied and documented. Hence, the study was done with the aim of assessing the effect of intra-articular (IA) injection of corticosteroid in patients with OA of the knee. Methods: This prospective observational study was conducted over a period of 6 months between 40 years and 75 years with Grade I and II OA of the knee admitted under the Department of Orthopaedics, Tertiary Care Hospital, Belgaum. Patients' affected knee was injected with 80 mg of triamcinolone after the examination, and follow-ups had done at 2 weeks, 6 weeks, 3 months, and 6 months. The standard pro forma used were Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: The mean age of the participants was 58.96 ± 9.58, ranging from 40 to 75 years, with a slightly higher proportion of females. The proportion of Grade 1 and Grade II OA was 24% and 76%, respectively, and 54.7% had right-sided involvement. The difference between pre Rx: Pre intervention VAS score VAS score and follow-up periods at 2 weeks, 6 weeks, 3 months, and 6 months was statistically significant with respect to VAS scale, KOOS scale, and WOMAC scale (P < 0.001). Conclusion: there was no major adverse effect of corticosteroid injections, and it showed significant improvement in patients. There is a need to conduct large-scale well-controlled clinical trials with an appropriate control group, to be able to document the relative efficacy and safety of IA steroid injection.